Huey "Piano" Smith and the Rocking Pneumonia Blues - Wirt, John (Book collections on Project MUSE., 2014)
Huey ""Piano"" Smith's musical legacy stands alongside that of fellow New Orleans legends Dr. John, Fats Domino, Ernie K-Doe, and Allen Toussaint. His 1957 classic, ""Rocking Pneumonia and the Boogie Woogie Flu, "" made Billboard's top R & B singles chart, and hundreds of artists including Aerosmith, the Grateful Dead, the Beach Boys, Johnny Rivers, and Chubby Checker have recorded his songs. The first biography of the artist responsible for hits ""Don't You Just Know It, "" ""High Blood Pressure, "" and ""Sea Cruise, "" Huey ""Piano"" Smith and the Rocking Pneumonia Blues follows the musi.